2011
DOI: 10.3389/fpsyg.2011.00195
|View full text |Cite
|
Sign up to set email alerts
|

Processing of voiced and unvoiced acoustic stimuli in musicians

Abstract: Past research has shown that musical training induces changes in the processing of supra-segmental aspects of speech, such as pitch and prosody. The aim of the present study was to determine whether musical expertise also leads to an altered neurophysiological processing of sub-segmental information available in the speech signal, in particular the voice-onset-time. Using high-density EEG-recordings we analyzed the neurophysiological responses to voiced and unvoiced consonant-vowel-syllables and noise-analogs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 62 publications
(92 reference statements)
8
52
0
2
Order By: Relevance
“…In nonmusicians, only one hub was located in peri-sylvian language regions. This indicates, therefore, a tendency at least toward more local clustering in the peri-sylvian brain area in RP musicians and supports the hypothesis that the brain of musicians is partly prepared to process auditory language information differently (see, for further support of this hypothesis, the special issue on the relation between music and language; Ettlinger, Margulis, & Wong, 2011;Giuliano, Pfordresher, Stanley, Narayana, & Wicha, 2011;Ott, Langer, Oechslin, Meyer, & Jäncke, 2011;Patel, 2011;Schon & Francois, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…In nonmusicians, only one hub was located in peri-sylvian language regions. This indicates, therefore, a tendency at least toward more local clustering in the peri-sylvian brain area in RP musicians and supports the hypothesis that the brain of musicians is partly prepared to process auditory language information differently (see, for further support of this hypothesis, the special issue on the relation between music and language; Ettlinger, Margulis, & Wong, 2011;Giuliano, Pfordresher, Stanley, Narayana, & Wicha, 2011;Ott, Langer, Oechslin, Meyer, & Jäncke, 2011;Patel, 2011;Schon & Francois, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…Currently, the intrinsic meaning of enhanced or reduced N1 amplitudes in musicians compared with nonmusicians is still a matter of debate. In fact, some studies reported larger N1 responses in musicians compared with nonmusicians (Ott, Langer, Oechslin, & Jäncke, 2011;Baumann et al, 2008;Kuriki, Kanda, & Hirata, 2006), whereas others did not reveal between-group differences (Lutkenhoner, Seither-Preisler, & Seither, 2006;Schneider et al, 2002) or reported reduced N1 amplitudes in musicians compared with nonmusicians (Kühnis et al, 2013a;Seppanen et al, 2012). Probably, these inconsistencies are driven by the selection of professional musicians, the spectral complexity of the stimuli, and the electrode location used for analyses.…”
Section: Introductionmentioning
confidence: 82%
“…This procedure has previously been used by our group (Elmer et al, 2012a;Kühnis, Elmer, Meyer, & Jäncke, 2012;Ott, Langer, Oechslin, Meyer, & Jäncke, 2012) and consisted of 30 successive trials in which participants had to compare pairs of piano melodies and to decide whether the heard melodies were equivalent, rhythmically different, or tonally different.…”
Section: Musical Aptitudesmentioning
confidence: 99%